Riluzole protects against skeletal muscle ischaemia-reperfusion injury in a porcine model. Issue 2 (February 2020) - Li, Rachel W.; Deng, Yi; Pham, Hai Nam; Weiss, Steven; Chen, Mingming; Smith, Paul N.
Highlights: Riluzole protects against microscopic cellular damage in ischaemia-reperfusion injury. DNA damage in ischaemia-reperfusion is dampened by Riluzole. Riluzole's effects can be explained by preserving glutathione levels and PARP activity. Abstract: Introduction: Skeletal muscle ischaemia-reperfusion injury (IRI) can be a life threatening condition. It is relevant to various aspects of the management of trauma and surgical patients. Currently there lacks a pharmacological agent that can be used to dampen the effects of IRI. Riluzole has been shown to reduce the effects of IRI on various organ systems, but there have yet to be any studies on the effects in IRI of skeletal muscle. Our aim was to investigate the effects of Riluzole on IRI in the skeletal muscle of pigs. Methods: Twenty-two pigs were randomly divided into groups. Riluzole was administered before ligation of the femoral artery to produce ischaemia in the tibialis anterior muscle in the experimental group but not the control group. The microscopic appearance of muscles were recorded, a TUNEL assay was used to identify DNA damage and glutathione levels were measured. Results: In the Riluzole group, muscle fibres appeared less wavy and less oedematous compared to the control group. The Riluzole group also had less evidence of DNA fragmentation on the TUNEL assay. The glutathione levels in the Riluzole group were also significantly greater than the control group. Discussion: Our findings suggest that Riluzole can potentially reduce the effects of IRI on skeletal muscle. This is potentially due to the ability of Riluzole to block sodium channels, decreasing action potentials and therefore glutamate release. It also acts to decrease intracellular calcium levels, which prevents apoptosis. Riluzole is a promising drug for the prevention of IRI in skeletal muscle, but further research is required.